The Level Of Islamic Financial Literacy And Islamic Financial Inclusion Of Students In The Islamic Capital Market - Herlina Yustati; Heri Junaidi; Asnaini Asnaini (UNIVED Press, 2024)
The purpose of this study was to determine the level of Islamic financial literacy and Islamic financial inclusion of students in Bengkulu Province, especially in Islamic capital market financial institutions. research methods with a quantitative approach survey method and data obtained through questionnaires given to 258 students in Bengkulu province who have a Sharia Investment Gallery. the results showed that the majority of Islamic financial literacy levels were at a moderate level (49%), as well as the slamic financial inclus level at a moderate level (45%).